Exploring Pakistani Doctors' Perspectives on Genetic Counseling: Challenges and Opportunities (Journal of Medical & Health Sciences Review, 2025)
Background: Genetic disorders pose a significant health burden globally due to high consanguinity rates and limited access to Genetic Counseling (GC) services.Objective: This study evaluates the acquaintance and perceived constraints of GC in Pakistani doctors. Moreover, it explores Pakistani doctors' familiarity, referral practices, perceived barriers and their possible solutions to enhance GC practice in Pakistan.Methods: A cross-sectional study was conducted using an online questionnaire to collect quantitative data, which was analyzed through descriptive statistics and thematic analysis.Results: Using a cross-sectional design, data from 52 doctors revealed that 41% of females were "very familiar" with GC, compared to 23.1% of males. The results indicate that all male doctors (100%) were familiar with GC, whereas 12.8% of female doctors reported a lack of familiarity with GC concept. Referral rates remained low, however, only 20.5% of female doctors and 7.7% of male doctors’ frequently referring patients for GC were reported. The key barriers cited were limited patient understanding and superstitious beliefs.Conclusion: Over 90% of doctors expressed interest in attending GC training and were in support of making it an integral part of healthcare services. In future, this implementation can strengthen patient access to GC, and doctor’s approach to informed decision-making about patient’s healthcare.